Biphasic roles of pentraxin 3 in cerebrovascular function after white matter stroke. (11th December 2020) - Shindo, Akihiro; Takase, Hajime; Hamanaka, Gen; Chung, Kelly K.; Mandeville, Emiri T.; Egawa, Naohiro; Maki, Takakuni; Borlongan, Mia; Takahashi, Ryosuke; Lok, Josephine; Tomimoto, Hidekazu; Lo, Eng H.; et al.
Abstract: Recent clinical studies suggest that pentraxin 3 (PTX3), which is known as an acute‐phase protein that is produced rapidly at local sites of inflammation, may be a new biomarker of disease risk for central nervous system disorders, including stroke. However, the effects of PTX3 on cerebrovascular function in the neurovascular unit (NVU) after stroke are mostly unknown, and the basic research regarding the roles of PTX3 in NVU function is still limited. In this reverse translational study, we prepared mouse models of white matter stroke by vasoconstrictor (ET‐1 or L‐Nio) injection into the corpus callosum region to examine the roles of PTX3 in the pathology of cerebral white matter stroke. PTX3 expression was upregulated in GFAP‐positive astrocytes around the affected region in white matter for at least 21 days after vasoconstrictor injection. When PTX3 expression was reduced by PTX3 siRNA, blood‐brain barrier (BBB) damage at day 3 after white matter stroke was exacerbated. In contrast, when PTX3 siRNA was administered at day 7 after white matter stroke, compensatory angiogenesis at day 21 was promoted. In vitro cell culture experiments confirmed the inhibitory effect of PTX3 in angiogenesis, that is, recombinant PTX3 suppressed the tube formation of cultured endothelial cells in a Matrigel‐based in vitro angiogenesis assay. Taken together, our findings may support a novel concept that astrocyte‐derived PTX3 plays biphasic roles in cerebrovascular function after white matter stroke; additionally, it may also provide a proof‐of‐concept that PTX3 could be a therapeutic target for white matter‐related diseases, including stroke.